Uma cidade para o capital: especulação imobiliária e déficit habitacional em Goiânia (1933-1964) - Mendes, Julianna Fernandes (2013)
This dissertation has as its object of study to identify the housing deficit in Goiania from 1933 to 1964 as well as its causes. For better understanding of the topic, the dissertation began with broader thinking about moving the capital of Goiás to Goiânia, in order to start the topic. The proposal is for a study of bibliography and sources, both provided by the IBGE (Brazilian Institute of Geography and Statistics) and the perception of authors and characters who witnessed the mentioned period. It was highlighted the issue of housing with their differences from person to person and perverse treatment of the state firing the worker. We emphasize that there has been no effective housing policy at both national and regional levels and the main propellant of urban spatial segregation that was the real estate capital, using various strategies of speculation, imposes its planning deletion. The creation of Goiânia was driven mainly by the real state capital; there were no other alternative with for the part of the population, regard to decent housing. Finally, we show that the real estate speculation led the process of housing deficit in the studied period, coming to spread throughout the entire life of the young Goiânia.